Oral Toxicity of Magnesium Oxide Nanoparticles, MgO NPs on Liver in Male Rats - Shafiq, Ayser Abdullah; Luaib, Noori Mohammed; Mahdi, Raghad Harbi; Alsaimary, Ihsan Edan (Iraqi Journal of Science, 2024)
Nanotechnology is an emerging technology that has led to the nanomedicine development, which involves nanoparticles that exist in the natural world. Nanoparticle is an ultrafine unit with dimensions measured in nanometers. They are created as a result of human activities, and have recently been used in various biomedical applications, consumer products, and commercially, etc. Magnesium oxide nanoparticles (MgO NPs), among the known metal oxides, have attracted a vast scientific interest. Therefore, human health can be at risk of continuous exposure. However, the toxic effects of MgO NPs should be assessed with their increased applications. The present study aimed to investigate the physiological and histological, alterations induced by the MgO nanoparticles in hepatocytes of male rats through oral route with (250, and 1000) mg/kg for (14, 28, and 56) days. Fifty-four male mature rats, (2.5 - 3 months old) were divided randomly into nine groups of six rats each, gavaged with MgO NPs (which were purchased from US Research Nanomaterials, Inc). The results obtained revealed highly significant increase (p<0.01) in aspartate aminotransferase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), and total bilirubin. The histopathological examinations showed sinusoidal dilatation, atrophy of hepatocytes, depletion of glycoprotein, focal area of necrosis, inflammatory cells infiltration and apoptosis. MgO NPs demonstrated potential harm to liver tissue, and human health.